2006
DOI: 10.1073/pnas.0607069103
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myosin binding protein c phosphorylation is cardioprotective

Abstract: Cardiac myosin binding protein C (cMyBP-C) has three phosphorylatable serines at its N terminus (Ser-273, Ser-282, and Ser-302), and the residues' phosphorylation states may alter thick filament structure and function. To examine the effects of cMyBP-C phosphorylation, we generated transgenic mice with cardiac-specific expression of a cMyBP-C in which the three phosphorylation sites were mutated to aspartic acid, mimicking constitutive phosphorylation (cMyBP-C AllP؉ ). The allele was bred into a cMyBP-C null b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
295
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(315 citation statements)
references
References 32 publications
16
295
4
Order By: Relevance
“…Post translational modifications, such as alterations in the phosphorylation status of sarcomeric and Z-disc proteins can result in altered cardiac contractility with progression to disease and death (11)(12)(13)(14). This is the first in vivo study investigating the functional role of cardiac ␣-Tm phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Post translational modifications, such as alterations in the phosphorylation status of sarcomeric and Z-disc proteins can result in altered cardiac contractility with progression to disease and death (11)(12)(13)(14). This is the first in vivo study investigating the functional role of cardiac ␣-Tm phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
“…Taken together, these in vitro data suggest that altering phosphorylation status affects the ability of Tm to cooperatively activate the thin filament upon binding of Ca 2ϩ to troponin (Tn). In recent years in vivo studies performed on animal models indicate that changes in the phosphorylation status of sarcomeric proteins such as troponin I (TnI), myosin binding protein C (MyBPC), and the regulatory myosin light chain result in alterations in Ca 2ϩ sensitivity of the myofilament and changes in cardiac function and may play a role in the development of cardiac disease (11)(12)(13)(14)(15). Investigation of a dilated cardiomyopathy transgenic (TG) mouse model bearing a human ␣-Tm mutation (E54K) shows that phosphorylation levels of Tm decrease relative to non-transgenic (NTG) littermates (16,17).…”
Section: Tropomyosin (Tm)mentioning
confidence: 99%
“…1A) (9, 10). β-Adrenergic-stimulated phosphorylation of these serines is believed to enhance cardiac contractility (11,12), and a high level of phosphorylation appears to be critical to normal cardiac function, whereas dephosphorylation has been associated with heart failure (13)(14)(15). Although the mechanistic role of cMyBP-C phosphorylation in vivo remains unclear, it is known to reduce the extensibility of the M-domain (10,16), diminish the binding of cMyBP-C to actin (17,18) and to myosin S2 (19), and to tune cMyBP-C's ability to modulate actomyosin activity in vitro (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…In this regard, cMyBP-C phosphorylation is significantly decreased during the development of heart failure and pathologic hypertrophy (10). More recently, it has been reported that cMyBP-C phosphorylation is cardioprotective when mouse hearts were subjected to ischemia and reperfusion injury (13). cMyBP-C is differentially phosphorylated at multiple sites by cAMP-dependent protein kinase A (PKA), protein kinase C (PKC) and Ca 2ϩ -calmodulin-activated kinase (10,14).…”
mentioning
confidence: 99%